The Principles of Democracy from an Islamic Perspective and Its Review in the Qur'an - Nur Aksin; Enur Nurjanah; Muhammad Rizki Kurniawan (Publikasi Indonesia, 2025)
Democracy from an Islamic perspective remains an ongoing debate among Muslim intellectuals. This research formulates the principles of democracy from an Islamic perspective and reviews them in the Quran. Issues related to Islam and democracy are still a matter of debate among Muslim intellectuals; some reject democracy with Islam because it is seen as contradictory, and some support Islam and democracy because it is in line with the concept of Shura. Therefore, it is necessary to understand the principles of democracy in Islam and the exorcism of democracy itself. The method used in this study is a qualitative literature review concerning primary data sources obtained from Google Scholars, especially those that discuss democracy in Islam. The findings show that Islam is not anti-democracy because the principles and principles in Islamic teachings support democracy. Democracy in Islam has principles that differ from democracy in the West. Among them are the principle of deliberation, the principle of equality, the principle of power as a mandate, and the principle of people's obedience. Democracy is vital in Islamic education, namely in respecting human values and developing creativity. This study concludes that democracy in Islam is not merely about a political system but also about the values of justice and the well-being of the ummah. This research implies the necessity of integrating Islamic values into modern democratic practices to align with Islamic teachings while maintaining the universal principles of democracy.